La Nouvelle-Orléans, une ville nommée Désir et bien davantage - Pascale SMORAG (E-REA)
Toponyms give insight into the geographical, political and cultural construction of a place. The French names of New Orleans express the Crown’s imperialist ambitions as well as the contradictions of the king’s colonial policy. The desire of the Spaniards, and later of the Americans to maintain this legacy, while simultaneously inscribing their own ambitions on the map, reveals the complexity of their commitment to the city. Current toponymic inspirations that mingle memory, pragmatism and romanticism prove how imbued with the cultures that shape them places are: at the same time they attest to the spatial dimension of cultures, which in the case of New Orleans contributes to the city’s "indomitable" identity.